External Assistance and Policies for Growth in Africa - Liuksila, Claire (Washington, D.C. : International Monetary Fund, 1995)
This booklet is a collection of papers presented at a seminar on policies for growth in Africa, held in Paris in February 1995 and sponsored by the Ministry of Finance of Japan. The seminar focused on four broad themes: how to enable the private sector to play a lead role in the growth process in Africa; how to boost domestic savings and help the financial sector to contribute to the mobilization and efficient us of resources; how to facilitate foreign aid and make it more effective; and, what are the essential elements of sound debt management practices?
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet